2006
DOI: 10.3758/bf03195920
|View full text |Cite
|
Sign up to set email alerts
|

Failures to find suppression of episodic memories in the think/no-think paradigm

Abstract: Anderson and Green (2001) had subjects learn paired associates and then selectively suppress responses to some of them. They reported a decrease in final cued recall for responses that subjects had been instructed not to think of and explained their data as resulting from cognitive suppression, a laboratory analog of repression. We report three experiments designed to replicate the suppression/repression results. After subjects learned a series of A-B word pairs (e.g., ordeal-roach), they were then asked to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 21 publications
7
109
4
Order By: Relevance
“…How do the substitutes work? As pointed out by others (Bulevich et al, 2006;Hertel & Calcaterra, 2005), the provision of substitutes corresponds to the AÁD phase in a retroactive-interference paradigm for paired-associate learning (Barnes & Underwood, 1959). In fact, we have recently found that the separate contribution of substitutes to forgetting, above effects of target suppression, has its counterpart in paired-associate learning in an experiment by Delprato and Garskof (1969).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…How do the substitutes work? As pointed out by others (Bulevich et al, 2006;Hertel & Calcaterra, 2005), the provision of substitutes corresponds to the AÁD phase in a retroactive-interference paradigm for paired-associate learning (Barnes & Underwood, 1959). In fact, we have recently found that the separate contribution of substitutes to forgetting, above effects of target suppression, has its counterpart in paired-associate learning in an experiment by Delprato and Garskof (1969).…”
Section: Discussionmentioning
confidence: 93%
“…In this final phase, regardless of previous instructions, participants are encouraged to recall all the originally learned targets in response to their cues. Anderson and Green's demonstrations of belowbaseline, suppression-induced forgetting on this test have been replicated by others (Anderson et al, 2004;Depue et al, 2006Depue et al, , 2007Hertel & Calcaterra, 2005;Joormann, Hertel, Brozovich, & Gotlib, 2005, Joormann, Hertel, LeMoult, & Gotlib, 2009Wessel, Wetzels, Jelicic, & Merckelbach, 2005), although failures to replicate have also been documented (e.g., Bulevich, Roediger, Balota, & Butler, 2006).…”
mentioning
confidence: 81%
“…Although, the negative control effect has been replicated many times, sometimes no reliable effect is observed even though it would be expected (e.g., Bulevich et al, 2006 ;Bergström, Velmans, de Fockert, & Richardson-Klavehn, 2007 ;Mecklinger, Parra, & Waldhauser, 2009 ;Hertel & Mahan, 2008 ;Hertel & Calcaterra, 2005 ) . For instance, Bulevich et al conducted three experiments with variants of the Think/ No-Think paradigm that closely paralleled earlier studies and observed 3%, 4%, and 1% negative control effects on the Same probe test, and similarly small effects on the Independent Probe test.…”
Section: The Negative Control Effect Sometimes Does Not Occurmentioning
confidence: 99%
“…Anderson and colleagues demonstrated a reliable amount of forgetting in the TNT procedure (see Anderson & Green, 2001;Anderson et al, 2004; for a summary of results from 687 participants, see Levy &, Anderson, 2008), while Bulevich, Roediger, Balota, and Butler (2006), Hertel and Calcaterra (2005), Mecklinger, Parra, and Waldhauser (2009), and Bergström, Velmans, de Fockert, and Richardson-Klavehn (2007) were not able to reproduce the TNT effect. There are two alternative explanations for TNT and the memory effects observed in it (when present).…”
mentioning
confidence: 99%